A Phonological Study of Juncture in Mosuli Arabic and Its Divergence from Some Kinds of Juncture in Standard Arabic - Israa Nadheer Saeed (Journal of College of Education, 2024)
Juncture as phonological process occurs in Mosuli Arabic. It is conceptual and exceptional. The conceptuality and exceptionality appear in two perspectives. The first one is in changing the phonological and morphological adoption of words if they are alone or within context, the second one is the role of juncture in camouflaging the main meaning of a word. These two perspectives seem natural, but the new truth is, that there is no constant rule to deduct how juncture occur in Mosuli Arabic. This study tackles how phonological phenomenon of juncture occurs in Mosuli Arabic, what is the nature of juncture in single words, and when it occurs in a sentence. The data of the study are collected by the researcher as a native speaker of Mosuli Arabic. The data represent most of words that are used by Mosuli people. The data have been analyzed in frame of prosody theory which includes how the phoneme and supra – segmental features work together in showing the behavior of juncture in Mosuli Arabic. One of the main findings in this study is, only three types of juncture existence in Mosuli Arabic. Another important finding is that juncture in Mosuli Arabic has substantial role in camouflaging information depending on the speaker's intention.
Keywords: Juncture - Categories - Camouflage - Divergence of some categories